ANALISIS DAMPAK PEMANFAATAN SUMBER DAYA INSANI DALAM MENDUKUNG GREEN ECONOMY (Studi Kasus Wisata Waduk Jeulikat Kota Lhokseumawe) - Cindy Silfana; Muhammad Ridwan; Annio Indah Lestari Nasution (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study examines, 1) how is the impact of the use of human resources on the community in Jeulikat Reservoir tourism and 2) what is the perception of Acehnese Muslims in supporting the Green Economy in Jeulikat Reservoir tourism, Lhokseumawe City?. This research uses a qualitative descriptive research type. The type of method used in this research is a case study, by analyzing and describing the data in the form of questions related to the use of human resources as a green economy in the city of Lhokseumawe. The informants who became the research subjects in this study were 2 people, namely tourism managers and the community. The results showed that the impact of the use of human resources on the community in Jeulikat Reservoir tourism, Lhokseumawe City had a positive or negative impact. Positive impacts: 1) provide a large enough job opportunity for the local community, 2) increase in community income, 3) since the existence of this tourist attraction, the gampong has a Gampong Original Income (PAG) which increases every year. The negative impact is that part of the community's land that was previously used for farming activities for the residents, has now been used as land for reservoir expansion, as a result, some community activities have stopped because the reservoir no longer functions as an irrigation channel. Meanwhile, the perception of Acehnese Muslims in supporting the Green Economy in Jeulikat Reservoir tourism in Lhokseumawe City is actually reflected in the opinions, desires, hopes and responses of the community on development activities in the area they live in.